Effects on Unsteady MHD Flow of a Nanofluid for Free Convection past an Inclined Plate - Gani, S. M. O.; Ali, M. Y.; Islam, M. A. (Journal of Scientific Research, 2022)
This paper deals with a similarity solution of unsteady magneto hydrodynamics two-dimensional boundary layer flow of a nanofluid for free convection past an inclined plate. Using similarity transformations, the governing equations are reduced into a set of non-linear ordinary differential equations. The transformed dimensionless equations are then solved numerically using the Nachtsheim-Swigert iteration technique and the order Runga-Kutta method. The effects of buoyancy-ratio parameter, Magnetic parameter, Brownian motion parameter, Thermophoresis parameter, Brownian diffusion parameter, unsteadiness, and other driving parameters on the velocity profile, temperature profile, and concentration profile are represented graphically and discussed in detail. The numerical values of several involved parameters on Skin-friction co-efficient, local Nusselt, and Sherwood numbers are presented in tabular form.